PROTOTYPE PENGONTROLAN PINTU OTOMATIS MENGGUNAKAN ARDUINO BERBASIS ANDROID - Dzar Faraby, Muhira; Ishak, Ishak; Ishak, Ishak; Rukiah, Rukiah; Rukiah, Rukiah; Setiawan, Setiawan; Setiawan, Setiawan (Jurnal Teknologi Terapan, 2016)
Effective and efficient is a way to facilitate the public in conducting activities, for example in terms of opening doors that are large, requires a lot of time and energy. Using Arduino, Android and PIR sensors are designed to make a protoype controlling automatic doors are controlled via Android via Bluetooth HC - 06 and can work automatically with the response detected by the PIR sensor. PIR sensors and Arduino serves as an input and as an output stepper motors to open and close the door. The working principle of this automatic door is in an android installed a software to control a door that has two modes. If the manual mode is activated, the door opens only when controlled using Android, when the automatic mode is activated the door will open when the sensor has detected the temperature of the human body that moves the door will open. The maximum distance control door is 1-50 meters in open space , but in a closed space that is controlling the maximum distance of 45 meters.